Wettable cathode and preparation method thereof

By combining calcium aluminate cement powder with dry mixing and cold pressing sintering, the difficulty in preparing TiB2 wettable cathodes was solved, and the preparation of high-performance, low-cost cathode materials was achieved to meet the needs of electrolytic applications.

CN120647390APending Publication Date: 2025-09-16ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511034900.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing methods for preparing TiB2 wettable cathodes have problems such as high cost, size limitation, difficulty in sintering, and complex preparation process. In addition, traditional sintering aids may affect the wettability and electrolytic performance of the cathode.

Method used

Calcium aluminate cement powder is used as a forming agent and sintering aid. A TiB2 wettable cathode is prepared through dry mixing, water spray stirring, cold pressing and inert atmosphere sintering. This eliminates the wet ball milling and degreasing steps, reduces the sintering temperature, and improves the density and wettability.

Benefits of technology

The preparation of low-cost, high-performance TiB2 wettable cathode has been achieved, which meets the requirements of electrolytic applications, simplifies the preparation process, reduces equipment investment and time costs, and improves the density and wettability of the cathode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120647390A_ABST
    Figure CN120647390A_ABST
Patent Text Reader

Abstract

The invention provides a wettable cathode and a preparation method thereof, and belongs to the field of aluminum electrolysis. The method comprises the following steps: performing dry mixing on TiB2 powder, calcium aluminate cement powder, a sintering aid and a dispersing agent according to a set proportion to obtain TiB2 mixed powder; adding water into the TiB2 mixed powder in a spraying manner, and stirring to obtain hydrated molded powder; carrying out compression molding on the hydrated molded powder through cold pressing to obtain a wettable cathode green body; and carrying out densification sintering on the wettable cathode green body to obtain the wettable cathode. By adding the calcium aluminate cement into the wettable cathode, the calcium aluminate cement can generate hydration reaction when meeting water and is low in melting point, the calcium aluminate cement plays a role of a forming agent in a powder raw material forming stage and plays a role of a sintering aid in a material sintering stage, so that the material preparation period can be shortened, the sintering temperature can be reduced, and the sintering density of the material can be improved; therefore, the invention provides the method for preparing the high-performance TiB2 wettable cathode in a short process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of aluminum electrolysis, and in particular to a wettable cathode and a preparation method thereof. Background Art

[0002] In the aluminum electrolysis industry, traditional carbon cathode materials have numerous limitations. Titanium boride (TiB2), an ideal wettable cathode material, is crucial for the development and application of both prebaked carbon anode and inert anode aluminum electrolysis technologies. For prebaked carbon anode aluminum reduction cells using a flow-through cathode (also known as a dry cathode) and inert anode aluminum reduction cells with a vertical electrode structure, since the cathode surface lacks the thick layer of molten aluminum found in conventional prebaked carbon anode aluminum reduction cells, a low-carbon, high-TiB2-content wettable cathode is essential. This ensures that the molten aluminum produced during the electrolysis process can properly precipitate and converge on the cathode surface. Furthermore, only low-carbon, high-TiB2-content wettable cathodes can prevent expansion and cracking caused by the penetration of sodium and potassium from the electrolyte melt, forming intercalation compounds (CmNam). Experimental studies have shown that pure TiB2 hot-pressed ceramics or TiB2-C composite hot-pressed ceramics with high TiB2 content can meet the requirements for wettable cathodes in electrolysis conditions with no or a thin molten aluminum layer. However, both ceramic cathodes have problems such as high cost, difficulty in production, and limited preparation size, making them difficult to promote and apply.

[0003] Using pressureless / cold pressing instead of hot pressing to prepare wettable TiB2 cathodes is one way to reduce costs and address size limitations. However, because TiB2 is difficult to sinter, a sintering aid is often required to lower the overall sintering temperature. Excessive use of sintering aids can affect cathode wettability and electrolytic performance, such as surface scarring or cracking during electrolysis, especially when the sintering aid is a metal powder or an oxide with a chemical activity lower than that of aluminum. When the sintering aid is a metal powder, the aluminum produced during electrolysis will alloy with it. This alloying reaction on the cathode surface thickens the aluminum melt, hindering its convergence. The alloying reaction caused by aluminum penetrating into the cathode interior can also generate internal stress, leading to material expansion and cracking. When the sintering aid is an oxide with a chemical activity lower than that of aluminum, excessive use of it may result in aluminothermic reduction reactions with aluminum. Even some borides, when introduced in large quantities, may undergo replacement reactions with aluminum, causing cracking in the cathode matrix. Furthermore, because pressureless / pressureless / cold-pressed sintering requires pre-pressing, the preparation process typically requires the addition of a binder. Furthermore, wet ball milling, drying, and granulation are required before pressing, adding to the cost and difficulty of preparation. In summary, the lack of technology for preparing high-performance TiB2 wettable cathodes using a short process remains a challenge for the industry. Summary of the Invention

[0004] The present application provides a wettable cathode and a preparation method thereof, so as to provide a method for preparing a high-performance TiB2 wettable cathode in a short process.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a wettable cathode, the method comprising:

[0006] TiB2 powder, calcium aluminate cement powder, sintering aid and dispersant are dry-mixed according to a set ratio to obtain TiB2 mixed powder;

[0007] Adding water to the TiB2 mixed powder by spraying and stirring to obtain a hydrated molded powder;

[0008] Pressing the hydrated forming powder into a shape by cold pressing to obtain a wettable cathode green body;

[0009] Densifying and sintering the wettable cathode green body under inert atmosphere to obtain a wettable cathode;

[0010] Wherein, the mass of the calcium aluminate cement powder is 3% to 12% of the total mass of the TiB2 mixed powder.

[0011] Optionally, the mass of the sintering aid is 0% to 5% of the total mass of the TiB2 mixed powder;

[0012] The mass of the dispersant is 0.5% to 1.0% of the total mass of the TiB2 mixed powder;

[0013] The mass of the TiB2 powder is 82% to 96.5% of the total mass of the TiB2 mixed powder.

[0014] Optionally, the sintering aid includes at least one of CuO, ZrB2, TiN, TiO2, CoB2, B and TiC; and / or,

[0015] The dispersant is an activated alumina dispersant.

[0016] Optionally, the purity of the calcium aluminate cement powder is greater than 99.9%, and the particle size is 200-500 mesh; and / or,

[0017] The sintering aid has a purity of >99.9% and a particle size of 200-500 mesh; and / or,

[0018] The dispersant has a purity of >99.9% and a particle size of 200-500 mesh; and / or,

[0019] The purity of the TiB2 powder is greater than 99.9%, and the particle size is 200 mesh to 500 mesh.

[0020] Optionally, the mass of the water is 5% to 10% of the total mass of the TiB2 mixed powder.

[0021] Optionally, the mixing time of the dry mixing is 4 hours to 6 hours; and / or,

[0022] The stirring method is one of ball milling, jar milling, and kneading, the stirring time is 3 minutes to 30 minutes, and the stirring temperature is 5° C. to 25° C.; and / or,

[0023] The time interval between the preparation of the hydrated molding powder and the completion of the compression molding is ≤1h.

[0024] Optionally, the press forming is performed using a hydraulic press or a cold isostatic press; wherein,

[0025] When the compression molding is performed using a hydraulic press, the compression molding pressure is 120 MPa to 200 MPa, and the holding time is 1 min to 3 min.

[0026] When a cold isostatic press is used for the pressing, the pressing pressure is 120 MPa to 200 MPa, and the holding time is 5 s to 30 s.

[0027] Optionally, after pressing the hydrated molding powder to obtain a wettable cathode green body, the method further comprises:

[0028] The wettable cathode green body is allowed to stand at a temperature of 5° C. to 25° C., a humidity of 30% to 80%, and a time of 4 hours to 24 hours.

[0029] Optionally, the temperature of the densification sintering is 1500° C. to 1700° C., and the holding time is 4 h to 6 h.

[0030] In a second aspect, the present application provides a wettable cathode prepared by the method described in any one of the embodiments of the first aspect, wherein the wettable cathode satisfies the following properties:

[0031] The density is 95.6% to 99.2%;

[0032] The sintering shrinkage is 10.4% to 14.7%;

[0033] In the KF-NaF-AlF3-Al2O3 electrolyte system, the 2 After running at a high cathode current density for 24 hours, the cathode remained intact and had good wettability with aluminum water.

[0034] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0035] The present invention provides a method for preparing a wettable cathode, comprising: dry-mixing TiB2 powder, calcium aluminate cement powder, a sintering aid, and a dispersant in a predetermined ratio to obtain a TiB2 mixed powder; spraying water into the TiB2 mixed powder and stirring the mixture to obtain a hydrated forming powder; cold-pressing the hydrated forming powder to obtain a wettable cathode green body; and densifying and sintering the wettable cathode green body under an inert atmosphere to obtain a wettable cathode; wherein the mass of the calcium aluminate cement powder is 3% to 12% of the total mass of the TiB2 mixed powder. The calcium aluminate cement powder component of the cathode sample undergoes a hydration reaction upon contact with water to form a calcium aluminate gel, which can be directly used as a forming agent to maintain green body strength without the need for adding a high molecular weight organic material (such as a resin). This eliminates the wet ball milling, drying, and granulation steps required in conventional processes that rely on organic forming agents, as well as the degreasing step during the sintering process, significantly shortening the process flow and reducing equipment investment and time costs. Furthermore, the calcium aluminate cement powder component of the cathode sample can serve as an auxiliary sintering agent. Its low-temperature melting property promotes particle diffusion, reduces the amount of traditional sintering aids, lowers the sintering temperature, and avoids excessive introduction of active metals (such as CuO and TiN) that trigger aluminothermic reduction reactions and lead to cathode cracking. This provides a short-process method for preparing high-performance TiB2 wettable cathodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0038] Figure 1 A schematic flow chart of a method for preparing a wettable cathode provided in an embodiment of the present application. DETAILED DESCRIPTION

[0039] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0040] The range descriptions described in this article, such as numerical ranges, ratio ranges, etc., include all possible sub-ranges and single numerical values ​​within the range. For example, the range description of "1 to 6" or "1~6" covers all sub-ranges from 1 to 6 (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6). Unless otherwise specified, the terms "including", "comprising", etc. used in this article mean "including but not limited to"; relational terms such as "first" and "second" are only used to distinguish different entities or operations, and do not imply an actual sequence or association relationship; "and / or" means that multiple situations can exist alone or at the same time; expressions such as "at least one", "multiple", and "at least one" refer to any combination of corresponding objects, including a combination of single or multiple objects. The proportional relationships involved in the article, such as mass ratios, molar ratios, etc., should be understood as the corresponding relationship between the first and second terms of the proportional formula in the order of description. The raw materials, reagents, instruments and equipment used in this article can be purchased on the market or prepared by existing methods.

[0041] Figure 1 A schematic flow chart of a method for preparing a wettable cathode provided in an embodiment of the present application.

[0042] like Figure 1 As shown, an embodiment of the present application provides a method for preparing a wettable cathode, the method comprising:

[0043] S1. Dry-mix TiB2 powder, calcium aluminate cement powder, sintering aid and dispersant according to a set ratio to obtain TiB2 mixed powder;

[0044] It should be noted that the core component of calcium aluminate cement powder is calcium aluminate (such as CaO·Al2O3, CaO·2Al2O3, etc.), which is made by grinding bauxite and limestone after high-temperature calcination. It has high chemical stability and heat resistance.

[0045] Through dry mixing of TiB2 mixed powder, the raw materials are evenly mixed to provide basic powder for subsequent hydration molding and sintering, ensuring the uniformity of composition.

[0046] In some embodiments, the mass of the calcium aluminate cement powder is 3% to 12% of the total mass of the TiB2 mixed powder.

[0047] In some embodiments, the mass of the sintering aid is 0% to 5% of the total mass of the TiB2 mixed powder;

[0048] The mass of the dispersant is 0.5% to 1.0% of the total mass of the TiB2 mixed powder;

[0049] The mass of the TiB2 powder is 82% to 96.5% of the total mass of the TiB2 mixed powder.

[0050] In some embodiments, the sintering aid includes: at least one of CuO, ZrB2, TiN, TiO2, CoB2, B and TiC; and / or,

[0051] The dispersant is an activated alumina dispersant.

[0052] In the examples of this application, TiB2 powder serves as the cathode material, imparting excellent conductivity, corrosion resistance, and wettability with molten aluminum. For example, the mass of the TiB2 powder can be 82%, 85%, 88%, 90%, 92%, 96.5%, or other amounts of the total mass of the TiB2 mixed powder.

[0053] In the embodiments of the present application, the hydration reaction of calcium aluminate cement is used to maintain the green strength and act as a forming agent. During the forming stage, a hydration reaction occurs when it comes into contact with water (forming calcium aluminate gel), maintaining the green strength, replacing traditional polymer forming agents, and eliminating the degreasing step. At the same time, during the sintering stage, it has a low melting point and can be used as an auxiliary sintering agent to promote diffusion between particles and increase density. Test results show that when the calcium aluminate cement content is less than 3wt.%, the green strength is low and it is easy to crack during the forming process. Since the chemical activity of calcium is higher than that of aluminum, the introduction of calcium aluminate cement will not increase the risk of the cathode undergoing aluminothermic reduction reaction during electrolytic application. However, the content of calcium aluminate cement should not be too high. When it is higher than 12wt.%, the sintering shrinkage of the cathode is significantly reduced, and the wettability of the cathode with molten aluminum is also affected. When the calcium aluminate cement content is high, more sintering aids need to be introduced to maintain the original shrinkage of the cathode sample. With an increase in sintering aids, especially an increase in oxides and borides whose chemical activity is lower than that of aluminum, the risk of the cathode cracking due to aluminothermic reduction reaction during electrolytic application will increase. Furthermore, the present application introduces calcium aluminate cement, eliminating the need for adding high-molecular-weight organic compounds as forming agents during the preparation of wettable cathode samples. This simplifies the conventional preparation process, including wet ball milling, drying, and granulation. Furthermore, degreasing is not required during the sintering process, significantly improving production efficiency and reducing production costs. For example, the mass of the calcium aluminate cement powder is 3%, 5%, 7%, 9%, 11%, 12%, and so on, of the total mass of the TiB2 mixed powder.

[0054] In the embodiments of the present application, the sintering aid can lower the sintering temperature and promote the sintering and densification of TiB2 particles (such as CuO, ZrB2, etc. can enhance particle bonding through liquid phase sintering or diffusion sintering), thereby improving the sintering shrinkage and density of the cathode sample, but the sintering aid should not be too much. The test results show that when the content of oxides and borides as sintering aids is within 5wt.%, they will not crack due to the occurrence of aluminothermic reduction reaction during the electrolytic application process. Exemplarily, the mass of the sintering aid is 0%, 1%, 2%, 3%, 4%, 5%, etc. of the total mass of the TiB2 mixed powder.

[0055] In the examples of this application, the dispersant (activated alumina) can reduce the amount of water required to hydrate the calcium aluminate cement, preventing over-wetting and agglomeration of the powder. It also prevents the calcium aluminate cement from agglomerating, ensuring mixing uniformity. When preparing the TiB2 mixture, the calcium aluminate cement and the activated alumina dispersant can be first mixed evenly, followed by mixing with the TiB2 powder and sintering aid. Exemplary amounts of the dispersant are 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, and so on, of the total mass of the TiB2 mixed powder.

[0056] In some embodiments, the mixing time of the dry mixing is 4 hours to 6 hours.

[0057] Limiting the dry mixing time to 4 to 6 hours can ensure that the powders are fully contacted and evenly dispersed, avoiding local composition deviations that affect subsequent molding and sintering performance. For example, the dry mixing time can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, etc.

[0058] In some embodiments, the calcium aluminate cement powder has a purity greater than 99.9% and a particle size of 200-500 mesh; and / or

[0059] The sintering aid has a purity of >99.9% and a particle size of 200-500 mesh; and / or,

[0060] The dispersant has a purity of >99.9% and a particle size of 200-500 mesh; and / or,

[0061] The purity of the TiB2 powder is greater than 99.9%, and the particle size is 200 mesh to 500 mesh.

[0062] The purity of all raw materials is >99.9% and the particle size is 200-500 mesh, ensuring the purity of raw materials and mixing uniformity, laying the foundation for subsequent performance.

[0063] S2, adding water to the TiB2 mixed powder by spraying, and stirring to obtain a hydrated molded powder;

[0064] The powder is initially combined through the hydration reaction of calcium aluminate cement to form a wet powder that can be pressed into shape.

[0065] In some embodiments, the mass of the water is 5% to 10% of the total mass of the TiB2 mixed powder.

[0066] Pure water is added to the TiB2 powder mixture at a total weight of 5-10 wt.% to facilitate hydration of the calcium aluminate cement and to moisten the entire mixture for compaction. Experimental results indicate that when the amount of pure water is less than 5 wt.%, the powder becomes dry and difficult to form, while when it exceeds 10 wt.%, the powder significantly agglomerates. Exemplary water amounts include 5%, 6%, 7%, 8%, 9%, 10%, and so on, of the total TiB2 powder mixture.

[0067] In some embodiments, the stirring method is one of ball milling, jar milling, and kneading, the stirring time is 3 minutes to 30 minutes, and the stirring temperature is 5°C to 25°C.

[0068] The mixing time is limited to 3 minutes to 30 minutes to ensure that the water and powder are evenly mixed and promote the full hydration reaction. A time greater than 3 minutes ensures that the calcium aluminate cement in the mixed powder can fully contact with the water. After more than 30 minutes, the initial hydration reaction of the calcium aluminate cement is basically completed, and the strength of the pressed green body will decrease. At the same time, 5°C to 25°C is the suitable range for the hydration reaction of calcium aluminate cement, so the ambient temperature during the mixing operation is more suitable in this range. For example, the stirring time can be 3 minutes, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc., and the stirring temperature can be 5°C, 10°C, 15°C, 20°C, 25°C, etc.

[0069] S3, pressing and molding the hydrated molding powder by cold pressing to obtain a wettable cathode green body;

[0070] The hydrated molding powder is pressed into a green body with a certain shape and strength through cold pressing, providing a basic form for subsequent sintering.

[0071] In some embodiments, the time interval between the preparation of the hydrated molding powder and the completion of the compression molding is ≤ 1 hour.

[0072] The hydration molding powder needs to be pressed within 1 hour to avoid excessive hydration reaction of calcium aluminate cement (causing powder hardening and decreased fluidity) and ensure smooth molding.

[0073] In some embodiments, the press forming is performed using a hydraulic press or a cold isostatic press; wherein,

[0074] When the compression molding is performed using a hydraulic press, the compression molding pressure is 120 MPa to 200 MPa, and the holding time is 1 min to 3 min.

[0075] When a cold isostatic press is used for the pressing, the pressing pressure is 120 MPa to 200 MPa, and the holding time is 5 s to 30 s.

[0076] The pressure of compression molding is limited to 120Mpa to 200Mpa. The external force causes the powder particles to be tightly packed, reducing the porosity and laying the foundation for sintering densification. If the pressure is lower than 120Mpa, the green body density is low; if the pressure is higher than 200Mpa, it will cause the particles to break or the green body to crack. The holding time of the hydraulic press is 1 to 3 minutes, and the holding time of the cold isostatic press is 5 to 30 seconds. This can ensure that the pressure is evenly transmitted to all parts of the powder and avoid local looseness. For example, the compression molding pressure is 120Mpa, 130Mpa, 140Mpa, 150Mpa, 160Mpa, 180Mpa, 200Mpa, etc. The holding time of the hydraulic press can be 1min, 1.5min, 2min, 2.5min, 3min, etc., and the holding time of the cold isostatic press can be 5s, 10s, 15s, 20s, 25s, 30s, etc.

[0077] In some embodiments, after pressing the hydrated molding powder to obtain a wettable cathode green body, the method further comprises:

[0078] The wettable cathode green body is allowed to stand at a temperature of 5° C. to 25° C., a humidity of 30% to 80%, and a time of 4 hours to 24 hours.

[0079] The green body can be left standing to fully promote the hydration reaction of calcium aluminate cement and continuously improve the green body strength (to avoid damage during subsequent handling or before sintering); the temperature and humidity conditions simulate the cement curing environment to optimize the hydration effect. For example, the standing temperature can be 5°C, 10°C, 15°C, 20°C, 25°C, etc., the humidity can be 30%, 40%, 50%, 60%, 70%, 80%, etc., and the standing time can be 4 hours, 8 hours, 12 hours, 16 hours, 18 hours, 24 hours, etc.

[0080] S4. Densifying and sintering the wettable cathode green body under inert atmosphere to obtain a wettable cathode;

[0081] High-temperature sintering eliminates pores and densifies the green body, forming a cathode material with high strength and excellent performance. At the same time, sintering is carried out under inert atmosphere to prevent TiB2 from being oxidized at high temperatures.

[0082] In some embodiments, the densification sintering temperature is 1500° C. to 1700° C., and the holding time is 4 h to 6 h.

[0083] 1500-1700°C is the appropriate sintering temperature for TiB2, which is sufficient to promote particle diffusion and grain boundary fusion while avoiding TiB2 decomposition. A holding time of 4-6 hours can ensure sufficient diffusion and improve density; if the time is shorter than 4 hours, the density will be insufficient; if the time is longer than 6 hours, it will cause abnormal grain growth and affect performance. For example, the temperature of densification sintering can be 1500°C, 1550°C, 1600°C, 1650°C, 1700°C, etc., and the holding time can be 4h, 4.5h, 5h, 5.5h, 6h, etc.

[0084] Based on a general inventive concept, the present application provides a wettable cathode prepared by the method described in any one of the above embodiments, wherein the wettable cathode satisfies the following properties:

[0085] The density is 95.6% to 99.2%;

[0086] The sintering shrinkage is 10.4% to 14.7%;

[0087] In the KF-NaF-AlF3-Al2O3 electrolyte system, the 2 After running at a high cathode current density for 24 hours, the cathode remained intact and had good wettability with aluminum water.

[0088] The wettable cathode is realized based on the above-mentioned method for preparing the wettable cathode. The specific steps of the method for preparing the wettable cathode can refer to the above-mentioned embodiment. Since the wettable cathode adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here.

[0089] In summary, this application, through the composite system of "calcium aluminate cement + low-amount sintering aid" combined with optimized cold pressing and sintering processes, achieves low-cost, large-scale preparation of TiB2 wettable cathodes while solving the problems of excessive sintering aids, complex processes, and insufficient performance in traditional cold pressing and sintering. The final product meets the requirements of electrolytic applications for density (95.6% to 99.2%), wettability, and stability, providing a feasible solution for the industrial application of TiB2 wettable cathodes. Specifically, this application has the following advantages:

[0090] (1) Process simplification and cost reduction: The traditional TiB2 cathode preparation requires the addition of high molecular weight organic matter as a forming agent, followed by degreasing (high temperature decomposition of organic matter), and involves complex processes such as wet ball milling, drying, and granulation. This method uses the hydration reaction of calcium aluminate cement (forming calcium aluminate gel) to directly maintain the strength of the green body, eliminating the degreasing step and skipping steps such as wet ball milling, significantly shortening the process flow. At the same time, the raw materials are evenly dispersed through dry mixing, reducing energy consumption and equipment investment, and lowering production costs.

[0091] (2) Material system innovation and performance optimization: Calcium aluminate cement has a dual role. It can be used as a forming agent substitute. The hydration reaction provides green strength and avoids cracking. It can also be used as an auxiliary sintering agent. Its low-temperature melting characteristics promote particle diffusion, reduce the amount of traditional sintering aids (only 0% to 5%), and avoid excessive introduction of active metals (such as CuO, TiN) to trigger aluminothermic reduction reactions and lead to cathode cracking. In addition, sintering in an inert atmosphere (1500-1700℃) inhibits TiB2 oxidation, achieves low oxygen content (<90ppm) and high density (95.6% to 99.2%), and improves corrosion resistance.

[0092] (3) Highly controllable sintering process: The sintering temperature (1500-1700°C) and holding time (4-6 hours) are optimized to ensure sufficient diffusion and densification of particles while preventing abnormal grain growth. The sintering shrinkage is stabilized at 10.4%-14.7%, matching the thermal expansion of the base material and reducing the risk of cracking.

[0093] (4) Excellent product performance: The TiB2 content reaches 82% to 96.5%, ensuring excellent wettability with molten aluminum. After 24 hours of electrolysis in a KF-NaF-AlF3-Al2O3 electrolyte, the material maintains excellent wettability, meeting the requirements of industrial electrolytic cells for cathode materials. Furthermore, the high-density TiB2 cathode exhibits excellent conductivity, reducing cathode voltage drop and electrolysis energy consumption.

[0094] (5) Improved safety and stability: Calcium in calcium aluminate cement is more chemically active than aluminum, and its introduction does not trigger aluminothermic reduction. Low amounts of sintering aids (≤5%) further reduce the risk of side reactions caused by active metals (such as CoB2 and TiC). Furthermore, static curing (5-25°C, 30%-80% humidity, 4-24 hours) fully enhances the strength of the hydrated green body and prevents breakage during handling or before sintering.

[0095] (6) Industrial application potential: Dry mixing and cold pressing simplify the process, are suitable for the preparation of large cathode blanks, and are easier to mass-produce.

[0096] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present application only and are not intended to limit the scope of the present application. The experimental methods in the following examples where specific conditions are not specified are generally measured according to industry standards. If there are no corresponding industry standards, then the methods are carried out according to general international standards, conventional conditions, or the conditions recommended by the manufacturer.

[0097] Example 1

[0098] This embodiment provides a method for preparing a wettable cathode, the method comprising the following steps:

[0099] S11, taking 96.5wt.% of TiB2 powder, 3wt.% of aluminate cement, and 0.5wt.% of activated alumina dispersant, dry-mixing them in a three-dimensional mixer for 4h, first mixing the calcium aluminate cement (CA270) and the activated alumina dispersant evenly, then adding the TiB2 powder and mixing evenly to obtain a TiB2 mixed powder;

[0100] S21. Add 5 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a pot mill and stir at an ambient temperature of 25° C. for 3 minutes to obtain a hydrated molded powder;

[0101] S31, after taking out, placing the hydrated molded powder into a mold, and maintaining the pressure at a pressing pressure of 200 MPa for 30 seconds in an isostatic press to obtain a wettable cathode green body, and then placing it in an environment with a temperature of 20° C. and a humidity of 30% for 4 hours;

[0102] S41, densifying and sintering the wettable cathode green body at 1700° C. in a 5N high-purity argon atmosphere, and keeping the temperature for 4 hours to obtain a wettable cathode;

[0103] After testing and analysis, the wettable cathode density is 95.6% and the sintering shrinkage is 10.4%.

[0104] The wettable cathode prepared according to the above process has a width * height * thickness = 45cm * 60cm * 1.6cm and is installed vertically in an inert anode aluminum electrolysis cell. It is matched with two inert anodes and is heated in a KF-NaF-AlF3-Al2O3 electrolyte system at 820℃ and a DC current of 20A. The cathode current density is 0.5A / cm 2 , run for 24 hours, the cathode is intact and well wetted with aluminum water.

[0105] Example 2

[0106] This embodiment provides a method for preparing a wettable cathode, the method comprising the following steps:

[0107] S11, taking 91wt.% TiB2 powder, 5wt.% aluminate cement, 2wt.% CuO, 1wt.% ZrB2, and 1wt.% activated alumina dispersant, dry-mixing them in a three-dimensional mixer for 6h, first mixing calcium aluminate cement (CA270) and activated alumina dispersant evenly, then adding TiB2 powder, CuO powder, and ZrB2 powder and mixing evenly to obtain TiB2 mixed powder;

[0108] S21. Add 7 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a pot mill, and stir at an ambient temperature of 15° C. for 5 minutes to obtain a hydrated molded powder;

[0109] S31, after taking out, placing the hydrated molded powder into a mold, and holding the pressing pressure at 150 MPa for 5 seconds in an isostatic press to obtain a wettable cathode green body, and then placing it in an environment with a temperature of 20° C. and a humidity of 60% for 6 hours;

[0110] S41. Densification sintering of the wettable cathode green body at 1500° C. in a 5N high-purity argon atmosphere and heat preservation for 6 hours to obtain a wettable cathode.

[0111] After testing and analysis, the wettable cathode density is 96.7% and the sintering shrinkage is 12.5%.

[0112] The wettable cathode prepared according to the above process has a width * height * thickness = 45cm * 60cm * 1.6cm and is installed vertically in an inert anode aluminum electrolysis cell. It is matched with two inert anodes and is heated in a KF-NaF-AlF3-Al2O3 electrolyte system at 820℃ and a DC current of 20A. The cathode current density is 0.5A / cm 2 , run for 24 hours, the cathode is intact and well wetted with aluminum water.

[0113] Example 3

[0114] This embodiment provides a method for preparing a wettable cathode, the method comprising the following steps:

[0115] S11, take 86wt.% TiB2 powder, 8wt.% aluminate cement, 3wt.% TiN, 2wt.% TiO2, and 1wt.% activated alumina dispersant, dry mix them in a three-dimensional mixer for 5h, first mix the calcium aluminate cement (CA270) and the activated alumina dispersant evenly, then add the TiB2 powder and TiN powder and mix evenly to obtain a TiB2 mixed powder;

[0116] S21. Add 8 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a ball mill, and stir at an ambient temperature of 20° C. for 10 minutes to obtain a hydrated molded powder.

[0117] S31. After taking out, the hydrated molded powder is placed in a mold and pressed in an isostatic press at a pressing pressure of 200 MPa for 30 seconds to obtain a wettable cathode green body, which is then placed in an environment with a temperature of 20° C. and a humidity of 80% for 12 hours.

[0118] S41. Densification sintering the wettable cathode green body at 1650° C. in a 5N high-purity argon atmosphere and keeping the temperature for 5 hours to obtain a wettable cathode.

[0119] After testing and analysis, the wettable cathode density is 97% and the sintering shrinkage is 13.5%.

[0120] The wettable cathode prepared according to the above process has a width * height * thickness = 45cm * 60cm * 1.6cm and is installed vertically in an inert anode aluminum electrolysis cell. It is matched with two inert anodes and is heated in a KF-NaF-AlF3-Al2O3 electrolyte system at 820℃ and a DC current of 20A. The cathode current density is 0.5A / cm 2 , run for 24 hours, the cathode is intact and well wetted with aluminum water.

[0121] Example 4

[0122] This embodiment provides a method for preparing a wettable cathode, the method comprising the following steps:

[0123] S11, taking 84wt.% TiB2 powder, 10wt.% aluminate cement, 1wt.% CoB2, 4wt.% B, and 1wt.% activated alumina dispersant, dry-mixing them in a ball mill at 200rpm for 4h to obtain a TiB2 mixed powder;

[0124] S21. Add 10 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a kneader, and stir for 10 minutes at an ambient temperature of 15° C. to obtain a hydrated molded powder;

[0125] S31. After taking out, the hydrated molded powder is placed in a mold and pressed in an isostatic press at a pressing pressure of 200 MPa for 30 seconds to obtain a wettable cathode green body, which is then placed in an environment with a temperature of 20° C. and a humidity of 60% for 24 hours.

[0126] S41. Densification sintering the wettable cathode green body at 1650° C. in a 5N high-purity nitrogen atmosphere and keeping the temperature for 5 hours to obtain a wettable cathode.

[0127] After testing and analysis, the wettable cathode density is 98.5% and the sintering shrinkage is 14.0%.

[0128] The wettable cathode prepared according to the above process has a width * height * thickness = 45cm * 60cm * 1.6cm and is installed vertically in an inert anode aluminum electrolysis cell. It is matched with two inert anodes and is heated in a KF-NaF-AlF3-Al2O3 electrolyte system at 820℃ and a DC current of 20A. The cathode current density is 0.5A / cm 2 , run for 24 hours, the cathode is intact and well wetted with aluminum water.

[0129] Example 5

[0130] This embodiment provides a method for preparing a wettable cathode, the method comprising the following steps:

[0131] S11, taking 82wt.% TiB2 powder, 12wt.% aluminate cement, 2wt.% CoB2, 3wt.% TiC, and 1wt.% activated alumina dispersant, dry-mixing them in a drum mixer at 50 rpm for 4 hours to obtain a TiB2 mixed powder;

[0132] S21. Add 10 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a kneader, and stir for 10 minutes at an ambient temperature of 20° C. to obtain a hydrated molded powder;

[0133] S31. After taking out, the hydrated molded powder is placed in a mold and pressed in a hydraulic press at a pressure of 120 MPa for 3 minutes to obtain a wettable cathode green body, which is then placed in an environment with a temperature of 20° C. and a humidity of 60% for 24 hours.

[0134] S41. Densification sintering the wettable cathode green body at 1650° C. in a 5N high-purity argon atmosphere and keeping the temperature for 5 hours to obtain a wettable cathode.

[0135] After testing and analysis, the wettable cathode density is 99.2% and the sintering shrinkage is 14.7%.

[0136] The wettable cathode prepared according to the above process has a width * height * thickness = 45cm * 60cm * 1.6cm and is installed vertically in an inert anode aluminum electrolysis cell. It is matched with two inert anodes and is heated in a KF-NaF-AlF3-Al2O3 electrolyte system at 820℃ and a DC current of 20A. The cathode current density is 0.5A / cm 2 , run for 24 hours, the cathode is intact and well wetted with aluminum water.

[0137] Comparative Example 1

[0138] This comparative example provides a method for preparing a wettable cathode, the method comprising the following steps:

[0139] S11, taking 97.5wt.% of TiB2 powder, 2wt% of aluminate cement, and 0.5wt% of activated alumina dispersant, dry-mixing them in a three-dimensional mixer to obtain a TiB2 mixed powder;

[0140] S21. Add 5 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a pot mill, and stir for 3 minutes at an ambient temperature of 30° C. to obtain a hydrated molded powder;

[0141] S31. After removal, the hydrated powder is placed in a mold and pressed in an isostatic press at a pressure of 200 MPa for 30 seconds to obtain a wettable cathode green body with chipped corners. The green body is then placed in an environment at a temperature of 20°C and a humidity of 30% for 4 hours.

[0142] S41. Densification sintering of the wettable cathode green body at 1700° C. in a 5N high-purity argon atmosphere and heat preservation for 4 hours to obtain a wettable cathode.

[0143] After testing and analysis, the wettable cathode density is 80.0% and the sintering shrinkage is 8.6%.

[0144] The wettable cathode prepared according to the above process has a width*height*thickness of 45cm*60cm*1.6cm. However, the cathode was not successfully produced due to the phenomenon of falling off or local cracking after multiple pressing and molding.

[0145] Comparative Example 2

[0146] This comparative example provides a method for preparing a wettable cathode, the method comprising the following steps:

[0147] S11, taking 83wt.% TiB2 powder, 15wt.% aluminate cement, 10wt.% CuO, and 2wt.% activated alumina dispersant, dry-mixing them in a three-dimensional mixer, first mixing the calcium aluminate cement and the activated alumina dispersant evenly, then adding the TiB2 powder and CuO powder and mixing evenly to obtain a TiB2 mixed powder;

[0148] S21. Add 12 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a pot mill, and stir for 10 minutes at an ambient temperature of 25° C. to obtain a hydrated powder. The powder is moist and severely agglomerated.

[0149] S31. Place the hydrated powder into a mold, flatten it, and compact it. Then, press it in an isostatic press at 200 MPa for 30 seconds to obtain a wettable cathode green compact. The green compact has an irregular morphology, with some areas thicker and some thinner. The green compact is then placed in an environment at 20°C and 60% humidity for 8 hours.

[0150] S41. Densification sintering of the wettable cathode green body at 1500°C was performed in a 5N high-purity argon atmosphere and kept warm for 4 hours to obtain a wettable cathode, but with many small cracks on the surface.

[0151] After testing and analysis, the wettable cathode density is 76.3% and the sintering shrinkage is 6.8%.

[0152] The wettable cathode prepared according to the above process has a width*height*thickness of 45cm*60cm*1.6cm. The cathode has an irregular morphology and many small cracks after firing, so the production was not successful.

[0153] Comparative Example 3

[0154] This comparative example provides a method for preparing a wettable cathode, the method comprising the following steps:

[0155] S11, take 76wt.% TiB2 powder, 15wt.% aluminate cement, 3wt.% CuO, 5wt.% CoB2, and 1wt.% activated alumina powder, dry mix them in a three-dimensional mixer, first mix the calcium aluminate cement and the activated alumina dispersant evenly, then add the TiB2 powder, CuO powder, and CoB2 powder and mix evenly to obtain a TiB2 mixed powder;

[0156] S21. Add 10 wt.% of pure water (deionized water) to the TiB2 mixed powder by spraying, place the mixture in a pot mill, and stir for 10 minutes at an ambient temperature of 25° C. to obtain a hydrated molded powder;

[0157] S31. Place the hydrated powder into a mold and press in an isostatic press at a pressure of 200 MPa for 30 seconds to obtain a wettable cathode green body. The green body is then placed in an environment at a temperature of 20° C. and a humidity of 60% for 8 hours.

[0158] S41. Densification sintering of the wettable cathode green body at 1500° C. in a 5N high-purity argon atmosphere and heat preservation for 4 hours to obtain a wettable cathode.

[0159] After testing and analysis, the wettable cathode density is 97.6% and the sintering shrinkage is 13.7%.

[0160] The wettable cathode prepared according to the above process has a width * height * thickness = 45cm * 60cm * 1.6cm and is installed vertically in an inert anode aluminum electrolysis cell. It is matched with two inert anodes and is heated in a KF-NaF-AlF3-Al2O3 electrolyte system at 820℃ and a DC current of 20A. The cathode current density is 0.5A / cm 2 After 24 hours of operation, the two edges of the cathode expanded and cracked.

[0161] Comparative Example 4

[0162] This comparative example is modified as follows based on Example 4:

[0163] When water was added and stirred, the ambient temperature exceeded 30°C, the calcium aluminate cement hydrated quickly, and the pressed green body had cracks. After being placed in an environment of 35°C for 24 hours, the cracks became larger.

[0164] Comparative Example 5

[0165] This comparative example is modified as follows based on Example 4:

[0166] When water was added and stirred, the ambient temperature was only 2°C. After the pressed green body was placed in an environment of -5°C to 3°C for 24 hours, the green body began to dry out and crack.

[0167] The density and sintering shrinkage of the wettable cathodes obtained in Examples 1 to 5 and Comparative Examples 1 to 3 are summarized, and the results are shown in Table 1.

[0168] Table 1 Density and sintering shrinkage of wettable cathodes of Examples 1 to 5 and Comparative Examples 1 to 3

[0169] Group density Sintering shrinkage Example 1 95.6 10.4 Example 2 96.7 12.5 Example 3 97.0 13.5 Example 4 98.5 14.0 Example 5 99.2 14.7 Comparative Example 1 80.0 8.6 Comparative Example 2 76.3 6.8 Comparative Example 3 97.6 13.7

[0170] As shown in Table 1, the wettable cathodes of Examples 1 to 5 have a density of 95.6% to 99.2%, and a sintering shrinkage of 10.4% to 14.7%.

[0171] The poor performance in Comparative Example 1 was due to the excessively high TiB2 content of 97.5%. The aluminate cement content, which acts as a sintering aid, was 2%, and the calcium aluminate cement content was less than 3 wt.%. This resulted in low green strength and prone to cracking during the molding process. Furthermore, the material was not sintered effectively during the sintering process, resulting in reduced sintered density and shrinkage.

[0172] The reason for the poor performance in Comparative Example 2 is that the TiB2 content is 83%, and the content of aluminate cement acting as a sintering aid is 15%. When the content is too high, and higher than 12 wt.%, the sintering shrinkage of the cathode is significantly reduced.

[0173] The reason for the poor performance in Comparative Example 3 is that the sintering aid content is too high, 3wt.% CuO, 5wt.% CoB2, 1wt.% activated alumina powder, and the sintering aid exceeds 5%, resulting in expansion and cracking due to the thermal reduction reaction during the electrolysis process.

[0174] In Comparative Example 4, the ambient temperature exceeded 30° C. when water was added and stirred. The temperature was too high and the hydration reaction was too fast, resulting in cracks in the green body.

[0175] In Comparative Example 5, the ambient temperature was only 2°C when water was added for stirring. The cracking of the pressed green body was aggravated after being placed in an environment of -5°C to 3°C for 24 hours. The ambient temperature was too low when water was added for stirring, and the hydration reaction of calcium aluminate cement was insufficient, resulting in cracking of the green body.

[0176] In addition, one or more technical solutions in the embodiments of the present application have at least the following technical effects or advantages:

[0177] (1) The wettable cathode is prepared by cold pressing and sintering, which is low-cost.

[0178] (2) During the preparation of the wettable cathode described in the present application, aluminate cement is added. Calcium aluminate cement can react with water to produce a hydration reaction and has a low melting point. It acts as a forming agent in the powder raw material forming stage and as a sintering aid in the material sintering stage. This can shorten the material preparation cycle, reduce the sintering temperature, and improve the sintering density of the material.

[0179] (3) Compared with the traditional TiB2-C composite cathode and the ordinary TiB2 coated cathode, it does not contain carbon, has better wettability with aluminum water and resistance to electrolyte melt and sodium and potassium penetration, is not easy to form an intercalation structure, and has a longer life.

[0180] (4) It can simultaneously meet the requirements of inert anode aluminum electrolysis technology and prebaked carbon anode aluminum electrolysis technology for wettable cathode under the conditions of thin aluminum liquid layer or no aluminum liquid layer.

[0181] (5) The present application provides a wettable cathode and a preparation method thereof, which replaces the high-cost hot pressing sintering with cold pressing sintering. By optimizing the composition and supplementing with a small amount of sintering aids and additives, the wet ball milling, drying, granulation, degreasing and other steps in the conventional preparation process are eliminated, and a carbon-free, low-porosity, high-strength TiB2-based composite cold-pressed sintered cathode sample is prepared.

[0182] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.

Claims

1. A method for preparing a wettable cathode, the method comprising: TiB2 powder, calcium aluminate cement powder, sintering aid and dispersant are dry-mixed according to a set ratio to obtain TiB2 mixed powder; Adding water to the TiB2 mixed powder by spraying and stirring to obtain a hydrated molded powder; Pressing the hydrated forming powder into a shape by cold pressing to obtain a wettable cathode green body; Densifying and sintering the wettable cathode green body under inert atmosphere to obtain a wettable cathode; Wherein, the mass of the calcium aluminate cement powder is 3% to 12% of the total mass of the TiB2 mixed powder.

2. The method according to claim 1, characterized in that The mass of the sintering aid is 0% to 5% of the total mass of the TiB2 mixed powder; The mass of the dispersant is 0.5% to 1.0% of the total mass of the TiB2 mixed powder; The mass of the TiB2 powder is 82% to 96.5% of the total mass of the TiB2 mixed powder.

3. The method according to claim 2, characterized in that The sintering aid includes: at least one of CuO, ZrB2, TiN, TiO2, CoB2, B and TiC; and / or, The dispersant is an activated alumina dispersant.

4. The wettable cathode according to claim 2, wherein The purity of the calcium aluminate cement powder is greater than 99.9%, and the particle size is 200-500 mesh; and / or, The sintering aid has a purity of >99.9% and a particle size of 200-500 mesh; and / or, The dispersant has a purity of >99.9% and a particle size of 200-500 mesh; and / or, The purity of the TiB2 powder is greater than 99.9%, and the particle size is 200 mesh to 500 mesh.

5. The method according to claim 1, characterized in that The mass of the water is 5% to 10% of the total mass of the TiB2 mixed powder.

6. The method according to claim 1, characterized in that The mixing time of the dry mixing is 4 hours to 6 hours; and / or, The stirring method is one of ball milling, jar milling, and kneading, the stirring time is 3 minutes to 30 minutes, and the stirring temperature is 5° C. to 25° C.; and / or, The time interval between the preparation of the hydrated molding powder and the completion of the compression molding is ≤1h.

7. The method according to claim 1, characterized in that The compression molding adopts a hydraulic press or a cold isostatic press; wherein, When the compression molding is performed using a hydraulic press, the compression molding pressure is 120 MPa to 200 MPa, and the holding time is 1 min to 3 min. When a cold isostatic press is used for the pressing, the pressing pressure is 120 MPa to 200 MPa, and the holding time is 5 s to 30 s.

8. The method according to claim 1, characterized in that After the hydrated forming powder is pressed and formed to obtain a wettable cathode green body, the method further comprises: The wettable cathode green body is allowed to stand at a temperature of 5° C. to 25° C., a humidity of 30% to 80%, and a time of 4 hours to 24 hours.

9. The method according to claim 1, characterized in that The temperature of the densification sintering is 1500° C. to 1700° C., and the holding time is 4 hours to 6 hours.

10. A wettable cathode prepared by the method according to any one of claims 1 to 9, wherein the wettable cathode satisfies the following properties: The density is 95.6% to 99.2%; The sintering shrinkage is 10.4% to 14.7%; In the KF-NaF-AlF3-Al2O3 electrolyte system, the 2 After running at a high cathode current density for 24 hours, the cathode remained intact and had good wettability with aluminum water.

Citation Information

Patent Citations

  • TiB2 / TiB composite ceramic cathode material for aluminum electrolysis and method for preparing the same

    CN104944959A

  • Composite material for moistened cathode of aluminium electrolytic cell

    RU2371523C1

  • Dense SiC ceramic products

    US5236875A